Solve the following equation. \[ \frac{1}{2}(x-3)=\frac{1}{3}(x+4) \] \( x=\square \) (Type an integer or a simplified fraction.)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To solve the equation \(\frac{1}{2}(x-3)=\frac{1}{3}(x+4)\), we start by eliminating the fractions. We can multiply both sides by 6 (the least common multiple of 2 and 3): \[ 6 \cdot \frac{1}{2}(x-3) = 6 \cdot \frac{1}{3}(x+4) \] This simplifies to: \[ 3(x-3) = 2(x+4) \] Expanding both sides gives: \[ 3x - 9 = 2x + 8 \] Next, we subtract \(2x\) from both sides: \[ 3x - 2x - 9 = 8 \] This simplifies to: \[ x - 9 = 8 \] Now, add 9 to both sides: \[ x = 17 \] Thus, the solution is: \[ x = 17 \]